INVESTITSIYALARNI FAOL JALB QILISHDA MOLIYA-KREDIT JARAYONLARINING AHAMIYATI - Madaminov In'omjon Ozodovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines the role and significance of financial and credit mechanisms in actively attracting investment to the national economy. During the study, commercial banks' investment credits, the impact of the refinancing rate on the investment environment, and intermediation processes in the financial market were statistically analyzed. Based on econometric analysis, a correlation (r=0,74) between financial and credit indicators and investment volume was identified. At the end of the article, scientific proposals and practical recommendations for transforming financial and credit processes to increase investment attractiveness were developed.